Lightweight automobile brake disc and manufacturing method thereof
By metallurgically joining the cap and disc body in the circumferential direction using ceramic reinforced aluminum base materials, the brake disc design addresses manufacturing challenges and enhances bonding strength, structural integrity, and wear resistance.
Patent Information
- Application Number
- JP2024547703
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-03-18
AI Technical Summary
Conventional lightweight brake discs for vehicles face challenges in manufacturing costs and complexity due to the need for a support structure and inserted connection members, which are prone to deformation and tearing under torque, affecting driving safety.
A lightweight brake disc design where the cap and disc body are metallurgically joined in the circumferential direction, using ceramic reinforced aluminum base materials with varying volume contents of ceramic phases, and specific alloy element contents to ensure effective bonding and reduced manufacturing complexity.
The solution achieves high interfacial bonding strength between the cap and disc body, reduces manufacturing costs and complexity, and enhances the structural strength and wear resistance of the brake disc, while maintaining safety and performance standards.
Smart Images

Figure 2025507377000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of brake discs, in particular to lightweight automotive brake discs. [Background technology]
[0002] Weight reduction is one of the most effective means to save energy in automobiles and other transport vehicles. By using high-performance light metal materials instead of steel materials for important moving parts such as engines and brake discs of transport equipment, it is possible to reduce the weight of the entire vehicle and the momentum of the high-speed moving parts of the transport equipment, as well as to significantly improve the dynamic performance of the transport equipment and reduce energy consumption.
[0003] Silicon carbide particle reinforced aluminum matrix composite materials have low density, high specific strength and rigidity, high thermal conductivity, and excellent wear resistance and corrosion resistance, and have broad future applications in the field of lightweight structural components. The replacement of traditional brake disc materials with silicon carbide particle reinforced aluminum matrix composite materials has also become the main research direction for reducing the weight of current transportation vehicles.
[0004] Conventional lightweight automobile brake discs are often made of aluminum alloy caps to achieve weight reduction, and the disc body is made of cast iron material with excellent wear resistance, which requires that the disc body and the cap can move radially relative to each other to minimize the thermal tension generated in the disc body during each braking process. The degree of radial freedom is generated by the engagement gap, which is generated by machining and inserting the connecting member, so that the manufacturing cost is high, and the inserted connecting member is easily deformed and broken due to the large torque during the braking process, which affects driving safety.
[0005] CN111442039A discloses a lightweight and wear-resistant aluminum-based powder metallurgy composite automobile brake disc, in which the disc body is made of an aluminum-based structural material, the friction surface is made of a wear-resistant aluminum-based composite material, and the friction surface and the disc body are made of different lightweight materials to further reduce the weight, meet the friction performance and reduce energy consumption. However, in the automobile brake disc, the disc body actually consists of a cap and a support structure extending radially outward from the cap between the two friction surfaces, which increases the contact area between the friction surface and the disc body, thereby improving the connection strength between the disc body and the friction surface. The existence of the support structure increases the manufacturing cost and the complexity of the manufacturing process. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention solves the problem of how to connect the disc body and the cap to meet the requirements of the operating conditions of the brake disc, when the disc body and the cap meet the respective processing needs and operating conditions. [Means for solving the problem]
[0007] Based on this, there is a need to provide a new lightweight automobile brake disc in which the disc body and the cap are metallurgically bonded in the circumferential direction, which can save the manufacturing cost of the support structure and simplify the manufacturing process.
[0008] A lightweight automotive brake disc includes a cap and a disc body, the cap and disc body being metallurgically bonded in a circumferential direction, the cap being made of a first aluminum-based material, the disc body being made of a second aluminum-based material, the first aluminum-based material comprising a ceramic reinforcing phase having a volume content of 0-30% and the remainder being an aluminum alloy matrix, the second aluminum-based material comprising a ceramic reinforcing phase having a volume content of 30-70% and the remainder being an aluminum alloy matrix, the alloying element content of the aluminum alloy matrix in the first aluminum-based material is equal to or less than the alloying element content of the aluminum alloy matrix in the second aluminum-based material, and when the alloying element content of the aluminum alloy matrix in the first aluminum-based material=the alloying element content of the aluminum alloy matrix in the second aluminum-based material, the volume contents of the ceramic reinforcing phase in the first aluminum-based material and the second aluminum-based material are not equal to each other.
[0009] In one embodiment, the aluminum alloy matrix is a 2- or 6-based aluminum alloy.
[0010] In one embodiment, the 2-type aluminum alloy is an Al-Cu-Mg-type alloy or an Al-Cu-Mg-Si-type alloy, and the 6-type aluminum alloy is an Al-Mg-Si-type alloy.
[0011] In one embodiment, the Al-Cu-Mg alloy is Al-4Cu-0.8Mg, the Al-Cu-Mg-Si alloy is Al-2Cu-0.5Mg-0.7Si-0.5Mn, and the Al-Mg-Si alloy is Al-0.6Mg-0.9Si or Al-1Mg-0.7Si-0.25Cu.
[0012] In one embodiment, the ceramic reinforcing phase in the first aluminum-based material is a ceramic reinforcing particle or a ceramic reinforcing fiber. When the ceramic reinforcing phase in the first aluminum-based material is a ceramic reinforcing particle, the average particle size of the ceramic reinforcing particle in the first aluminum-based material is 10 μm to 40 μm. When the ceramic reinforcing phase in the first aluminum-based material is a ceramic reinforcing fiber, the aspect ratio of the ceramic reinforcing fiber in the first aluminum-based material is 5 to 10, and the diameter of the ceramic reinforcing fiber is 50 μm or less.
[0013] In one embodiment, the ceramic reinforcing phase in the second aluminum-based material is a ceramic reinforcing particle, and the ceramic reinforcing particle in the second aluminum-based material has an average particle size of 45 μm to 100 μm, more preferably 45 μm to 75 μm.
[0014] In one embodiment, the ceramic reinforcing phase is at least one selected from the group consisting of carbides, nitrides, oxides, silicides and borides.
[0015] In one embodiment, the cap includes a cap body and a flange portion, the disk body includes a friction portion and a connection portion, and an axially outer wall of the flange portion and an axially inner wall of the connection portion are metallurgically joined in the circumferential direction.
[0016] In one embodiment, the axially outer wall of the flange portion is provided with a plurality of protrusions or receiving openings along a circumferential direction, and correspondingly, the axially inner wall of the connection portion is provided with a plurality of receiving openings or protrusions along a circumferential direction, and when the flange portion and the connection portion are metallurgically joined, the protrusions are provided within the receiving openings.
[0017] In one embodiment, the length of the projection is parallel to or at an included angle with the radial direction of the brake disc.
[0018] By providing the protrusion, the contact area between the flange and the connection portion can be increased, and the interface bonding strength between the cap and the disk body can be further increased.
[0019] In one embodiment, a plurality of protrusions are provided along the circumferential direction on the axially outer wall of the flange, and a receiving port is provided along the circumferential direction on the axially inner wall of the connection part. The length direction of the protrusions is provided at an included angle of 5° to 10° with the radial direction of the brake disc. By extending the protrusions outward slightly offset from the radial direction, deformation can be mitigated and the interface bonding strength between the cap and the disc body can be further improved.
[0020] Further, the circumferential width of each of the protrusions gradually decreases or gradually increases along the extension direction (i.e., along its length), or the circumferential width of each of the protrusions first decreases, then increases, and then decreases again along the extension direction.
[0021] In one embodiment, the axial thickness of the protrusion is the same as the axial depth of the receiving opening and is less than or equal to the axial thickness of the friction portion.
[0022] In addition, the present application further provides a method for manufacturing the above-mentioned lightweight automobile brake disc, and the specific solutions are as follows:
[0023] The manufacturing method of the lightweight automobile brake disc is as follows: providing the first aluminum-based material and a second aluminum-based material; and pre-pressing the first and second aluminum-based materials respectively, or pre-pressing one of them and filling the other with powder, followed by laminating, sintering and hot pressing to obtain the lightweight automotive brake disc.
[0024] In one embodiment, the pre-pressure molding pressure is 30 MPa to 70 MPa, and the laminating pressure is 200 MPa to 400 MPa, and more preferably 200 MPa to 300 MPa.
[0025] In one embodiment, the sintering conditions are to increase the temperature to 570°C to 640°C at a rate of 5°C / min to 10°C / min and to keep the temperature for 0.5 to 2 hours, and more preferably to increase the temperature to 580°C to 600°C and to keep the temperature for 0.5 to 2 hours.
[0026] In one embodiment, the hot press forming is performed at a temperature of 530° C. to 570° C. and a pressure of 200 MPa to 300 MPa. Effect of the Invention
[0027] In the above-mentioned lightweight automobile brake disc, the cap is made of a first aluminum-based material having a ceramic reinforcing phase with a volume content of 0-30% and the remainder being an aluminum alloy matrix, and the disc body is made of a second aluminum-based material having a ceramic reinforcing phase with a volume content of 30-70% and the remainder being an aluminum alloy matrix. The alloying element content of the aluminum alloy matrix in the first aluminum-based material is controlled to be equal to or less than the alloying element content of the aluminum alloy matrix in the second aluminum-based material, and at the same time, when the alloying element content of the aluminum alloy matrix in the first aluminum-based material=the alloying element content of the aluminum alloy matrix in the second aluminum-based material, the volume contents of the ceramic reinforcing phase in the first aluminum-based material and the second aluminum-based material are controlled so as not to be equal. This makes it possible to match the sintering shrinkage rates of the first aluminum-based material and the second aluminum-based material during the powder metallurgy manufacturing process, and to prevent defects such as cracks from occurring during the manufacturing process. At the same time, the thermal expansion coefficients of the first aluminum-based material and the second aluminum-based material during the use of the automobile brake disc are also matched, so that a high interfacial bonding strength can be obtained by metallurgically joining the cap and the disc body only in the circumferential direction.
[0028] At the same time, the cap is made of a first aluminum-based material having a ceramic reinforcing phase with a volume content of 0-30% and the remainder being an aluminum alloy matrix, which has high strength and good processability, and can avoid the difficulty in forming caused by ceramic-reinforced aluminum-based composite materials with a high volume content. The disc body is made of a second aluminum-based material having a ceramic reinforcing phase with a volume content of 30-70% and the remainder being an aluminum alloy matrix, which has good wear resistance and heat resistance and can meet the braking performance requirements such as friction wear resistance and fatigue resistance required for the friction braking process of conventional automotive brake discs.
[0029] Furthermore, compared to an automobile brake disc structure in which a cap and a disc body are connected in the axial direction, the lightweight automobile brake disc of the present application omits the manufacture of a support structure between the friction surfaces, and the cap and the disc body are both manufactured from an aluminum-based composite material with an aluminum alloy matrix, making it lightweight, and there is no need to set pressures for the cap and the disc body separately during lamination, simplifying the equipment design, saving manufacturing costs, and simplifying the manufacturing process, and also avoiding the occurrence of steps at the interface bonding points due to different pressures during the lamination process, which could affect the molding of the brake disc. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a schematic diagram showing the structure of a lightweight automobile brake disc according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of the lightweight automobile brake disc shown in FIG. [Diagram 3] FIG. 2 is an exploded view of the lightweight automobile brake disc shown in FIG. [Figure 4] FIG. 4 is a structural schematic diagram of a lightweight automobile brake disc according to another embodiment. [Diagram 5] FIG. 5 is a cross-sectional view of the lightweight automobile brake disc shown in FIG. [Figure 6]FIG. 5 is an exploded view of the lightweight automobile brake disc shown in FIG. 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] In the following, in order to facilitate understanding of the present invention, the present invention will be described more completely and preferred embodiments of the present invention will be shown. However, the present invention can be realized in various forms and is not limited to the embodiments described herein. Rather, these embodiments are provided for the purpose of providing a more thorough and comprehensive understanding of the present disclosure.
[0032] In this context, "axial direction" refers to the direction parallel to the central axis of rotation of the brake disc, "radial direction" refers to the direction perpendicular to the central axis of rotation of the brake disc, and "circumferential direction" refers to the circumferential direction of the disc body.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in describing the present invention are used only for the purpose of describing specific examples and are not intended to limit the present invention.
[0034] 1 to 3, a lightweight automobile brake disc 10 according to one embodiment is provided, and the lightweight automobile brake disc 10 includes a cap 110 and a disc body 120. The cap 110 includes a cap body 112 and a flange portion 114, and the disc body 120 includes a friction portion 122 and a connection portion 124, and an axially outer wall of the flange portion 114 and an axially inner wall of the connection portion 124 are metallurgically joined in the circumferential direction, thereby realizing metallurgical joining between the cap 110 and the disc body 120 in the circumferential direction.
[0035] Specifically, the axial outer wall of the flange portion 114 is provided with several protrusions 1142 uniformly distributed along the circumferential direction, the protrusions 1142 extending outward, and the longitudinal direction of the protrusions 1142 is arranged at an included angle of (5° to 10°) with respect to the radial direction of the brake disc. The connecting portion 124 is provided with receiving openings 1242 that match the protrusions 1142, and each protrusion 1142 is tightly received in the corresponding receiving opening 1242, and the axial side wall of each receiving opening 1242 is metallurgically joined to the axial side wall of the corresponding protrusion 1142, thereby metallurgically joining the axial outer wall of the flange portion 114 and the axial inner wall of the connecting portion 124 in the circumferential direction.
[0036] By providing the above-mentioned protrusion 1142, the contact area between the flange portion 114 and the connecting portion 124 can be increased, thereby increasing the interfacial bonding strength between the flange portion 114 and the connecting portion 124. Furthermore, high interfacial bonding strength can be obtained simply by metallurgically joining the cap 110 and the disk body 120 in the circumferential direction.
[0037] In this embodiment, the protrusions 1142 extend outwardly at a slight radial offset, thereby mitigating deformation to some extent and extending the service life of the brake disc.
[0038] In this embodiment, the circumferential width of each protrusion 1142 gradually decreases along the extension direction (ie, the length direction) and is formed in an arc shape or a sawtooth shape.
[0039] In other embodiments, the circumferential width of each protrusion 1142 may gradually expand along the extension direction, thereby forming an interlocking structure between the flange portion 114 and the connecting portion 124, and further increasing the connection strength between the cap 110 and the disk body 120.
[0040] Furthermore, the axial thickness of the protrusion 1142 is the same as the axial depth of the receiving port 1242 and is equal to or smaller than the axial thickness of the friction portion 122. When the axial thickness of the protrusion 1142 is smaller than the axial thickness of the friction portion 122, this is advantageous for heat dissipation and debris discharge from the friction portion 122.
[0041] In the above-mentioned lightweight automobile brake disc 10, the cap 110 is made of a first aluminum-based material, and the disc body 120 is made of a second aluminum-based material, and a specific manufacturing method thereof includes the following steps S110 to S130.
[0042] In S110, a first aluminum-based material and a second aluminum-based material are provided.
[0043] Here, if the first aluminum-based material is composed of a ceramic reinforcing phase with a volume content of 0-30% and the remainder being an aluminum alloy matrix, and the second aluminum-based material is composed of a ceramic reinforcing phase with a volume content of 30-70% and the remainder being an aluminum alloy matrix, and the alloying element content of the aluminum alloy matrix in the first aluminum-based material is less than or equal to the alloying element content of the aluminum alloy matrix in the second aluminum-based material, and the alloying element content of the aluminum alloy matrix in the first aluminum-based material=the alloying element content of the aluminum alloy matrix in the second aluminum-based material, then the volume contents of the ceramic reinforcing phases in the first aluminum-based material and the second aluminum-based material are not equal.
[0044] The above alloying element contents are based on the aluminum alloy matrix and refer to mass contents.
[0045] Furthermore, the aluminum alloy matrix is a 2-type or 6-type aluminum alloy. The 2-type aluminum alloy is an aluminum alloy containing copper as the main alloying element, and includes Al-Cu-Mg-type alloys and Al-Cu-Mg-Si-type alloys, while the 6-type aluminum alloy is an aluminum alloy containing magnesium and silicon as the main alloying elements and a Mg2Si phase as a strengthening phase, and includes Al-Mg-Si-type alloys.
[0046] Furthermore, the Al-Mg-Si alloy is Al-1Mg-0.7Si-0.25Cu (i.e., the alloy is mainly composed of 1% by mass of Mg, 0.7% by mass of Si, 0.25% by mass of Cu, and the balance being Al) or Al-0.6Mg-0.9Si (i.e., the alloy is mainly composed of 0.6% by mass of Mg, 0.9% by mass of Si, and the balance being Al). The Al-Cu-Mg alloy is Al-4Cu-0.8Mg (i.e., the alloy is mainly composed of 4% by mass of Cu, 0.8% by mass of Mg, and the balance being Al). The Al-Cu-Mg-Si alloy is Al-2Cu-0.5Mg-0.7Si-0.5Mn (i.e., the alloy is mainly composed of 2% by mass of Cu, 0.5% by mass of Mg, 0.7% by mass of Si, 0.5% by mass of Mn, and the remainder being Al).
[0047] The aluminum alloy matrix in the first aluminum-based material and the aluminum alloy matrix in the second aluminum-based material may be of the same system or different systems, and it is only necessary to control the volume contents of the ceramic reinforcing phase in the first aluminum-based material so that the alloying element content of the aluminum alloy matrix in the first aluminum-based material is equal to or less than the alloying element content of the aluminum alloy matrix in the second aluminum-based material, and in the case where the alloying element content of the aluminum alloy matrix in the first aluminum-based material=the alloying element content of the aluminum alloy matrix in the second aluminum-based material, the volume contents of the ceramic reinforcing phase in the first aluminum-based material and the second aluminum-based material are not equal to each other.
[0048] Furthermore, the ceramic reinforcing phase in the first aluminum-based material may be ceramic reinforcing particles or ceramic reinforcing fibers. When the ceramic reinforcing phase in the first aluminum-based material is ceramic reinforcing particles, the ceramic reinforcing particles have an average particle size of 10 μm to 40 μm. When the ceramic reinforcing phase in the first aluminum-based material is ceramic reinforcing fibers, the ceramic reinforcing fibers have an aspect ratio of 5 to 10 and a diameter of 50 μm or less.
[0049] The ceramic reinforcing phase in the second aluminum-based material may be ceramic reinforcing particles, and the ceramic reinforcing particles have an average particle size of 45 μm to 100 μm, and more preferably 45 μm to 75 μm.
[0050] Furthermore, the ceramic reinforcing phase is at least one selected from the group consisting of carbides (e.g., TiC, SiC, B4C, etc.), nitrides (e.g., Si3N4), oxides (e.g., Al2O3), silicides (e.g., Ti5Si3), and borides (e.g., TiB, TiB2, etc.).
[0051] It should be noted that the ceramic reinforcing phase in the first aluminum-based material and the ceramic reinforcing phase in the second aluminum-based material may be the same or different.
[0052] In S120, the first aluminum-based material is put into a cap mold and pre-pressurized to obtain a pre-pressurized blank of a cap; and at the same time, the second aluminum-based material is put into a disk body mold and pre-pressurized to obtain a pre-pressurized blank of a disk body; Alternatively, the first aluminum-based material is put into a cap mold and pre-pressurized, and then the second aluminum-based material is filled into a disk body mold correspondingly; The pre-pressure molding pressure in step S120 is 30 MPa to 70 MPa.
[0053] In S130, lamination, sintering and hot press molding are then carried out to obtain a lightweight automotive brake disc.
[0054] Here, the pressure for lamination is 200MPa to 400MPa. Sintering conditions are heating to 570℃ to 640℃ at a heating rate of 5℃ / min to 10℃ / min and keeping the temperature for 0.5 to 2 hours. Hot press molding is performed at a temperature of 530℃ to 570℃ and a pressure of 200MPa to 300MPa.
[0055] More preferably, the lamination pressure is 200 MPa to 300 MPa. As sintering conditions, the temperature is increased to 580° C. to 600° C. at a rate of 5° C. / min to 10° C. / min, and the temperature is maintained for 0.5 to 2 hours.
[0056] The lightweight automobile brake disc 10 may be manufactured by other methods as long as the cap 110 and the disc body 120 can be metallurgically joined in the circumferential direction.
[0057] 4 to 6, there is provided a lightweight automobile brake disc 20 according to another embodiment, which includes a cap 210 and a disc body 220. The cap 210 includes a cap body 212 and a flange portion 214, and the disc body 220 includes a friction portion 222 and a connection portion 224, and an axially outer wall of the flange portion 214 and an axially inner wall of the connection portion 224 are metallurgically joined in the circumferential direction, thereby realizing metallurgical joining between the cap 210 and the disc body 220 in the circumferential direction.
[0058] More preferably, the axially outer wall of the flange portion 214 is provided with several protrusions 2142 uniformly distributed along the circumferential direction, the longitudinal direction of the protrusions 2142 is parallel to the radial direction of the brake disc (i.e., the protrusions extend outward along the radial direction), the connecting portion 224 is provided with receiving openings 2242 matching the protrusions 2142, each protrusion 2142 is closely received in the corresponding receiving opening 2242, and the axial side wall of each receiving opening 2242 is metallurgically joined to the axial side wall of the corresponding protrusion 2142, thereby metallurgically joining the axially outer wall of the flange portion 214 and the axially inner wall of the connecting portion 224 in the circumferential direction.
[0059] By providing several radially outward extending protrusions 2142 uniformly distributed along the circumferential direction on the axially outer wall of the flange portion 214, the contact area between the flange portion 214 and the connecting portion 224 can be increased, and the interfacial bonding strength between the flange portion 214 and the connecting portion 224 can be improved.
[0060] Furthermore, in this embodiment, the circumferential width of each protrusion 2142 first decreases along the extension direction, then increases, and then decreases again, thereby forming a structure in which the flange portion 214 and the connecting portion 224 engage with each other, further increasing the connection strength between the cap 210 and the disc body 220.
[0061] Furthermore, the axial thickness of the protrusion 2142 is the same as the axial depth of the receiving port 2242 and is equal to or smaller than the axial thickness of the friction portion 222. When the axial thickness of the protrusion 2142 is smaller than the axial thickness of the friction portion 222, this is advantageous for heat dissipation and debris discharge from the friction portion 222.
[0062] The specific manufacturing method of the above-mentioned lightweight automobile brake disc 20 is the same as steps S110 to S130, and therefore the description thereof will be omitted here.
[0063] The effects of the volume content of the ceramic reinforcing phase in the composition and the alloying element content in the aluminum alloy matrix on the finished product of the lightweight automotive brake disc according to the present invention will be described below using examples and comparative examples. Example 1
[0064] In this example, the structural form shown in Figures 1 to 3 was used, the first aluminum-based material was made of Al-3Cu-0.8Mg, the second aluminum-based material was made of silicon carbide particles with a volume content of 30% and the remainder Al-4Cu-0.8Mg, and the average particle size of the silicon carbide particles in the second aluminum-based material was 45 µm.
[0065] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the lightweight automobile brake disc was 200 MPa or more. The lightweight automobile brake disc was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 2
[0066] In this embodiment, the structural form shown in Figures 1 to 3 was used, the first aluminum-based material consisted of silicon carbide particles with a volume content of 5% and the remainder Al-1Mg-0.7Si-0.25Cu, the second aluminum-based material consisted of silicon carbide particles with a volume content of 35% and the remainder Al-4Cu-0.8Mg, the silicon carbide particles in the first aluminum-based material had an average particle size of 10 µm, and the silicon carbide particles in the second aluminum-based material had an average particle size of 50 µm.
[0067] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 180 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 3
[0068] 2 to 4, the first aluminum-based material is made of 10% silicon carbide reinforcing fibers by volume and the remainder is Al-2Cu-0.5Mg-0.7Si-0.5Mn, and the second aluminum-based material is made of 40% silicon carbide reinforcing particles by volume and the remainder is Al-2Cu-0.5Mg-0.7Si-0.5Mn. The aspect ratio of the silicon carbide reinforcing fibers in the first aluminum-based material is 5, and the diameter is 50 μm or less, and the average particle size of the silicon carbide reinforcing particles in the second aluminum-based material is 50 μm.
[0069] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 150 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 4
[0070] In this embodiment, the axially outer wall of the flange and the axially inner wall of the connection part are directly metallurgically joined in the circumferential direction (i.e., no protrusions or receiving openings are provided), the first aluminum-based material is composed of 15% by volume of Si3N4 reinforcing fibers and the remainder Al-1Mg-0.7Si-0.25Cu, and the second aluminum-based material is composed of 50% by volume of Si3N4 reinforcing particles and the remainder Al-2Cu-0.5Mg-0.7Si-0.5Mn. The Si3N4 reinforcing fibers in the first aluminum-based material have an aspect ratio of 7 and a diameter of 50 μm or less, and the Si3N4 reinforcing particles in the second aluminum-based material have an average particle size of 55 μm.
[0071] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 150 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 5
[0072] In this example, the structure shown in Figures 2 to 4 was used, the first aluminum-based material was made of Al2O3 reinforcing fibers with a volume content of 20% and the remainder Al-0.6Mg-0.9Si, and the second aluminum-based material was made of Al2O3 reinforcing particles with a volume content of 50% and the remainder Al-4Cu-0.8Mg. The aspect ratio of the Al2O3 reinforcing fibers in the first aluminum-based material was 10, and their diameters were 50μm or less, and the average particle size of the Al2O3 reinforcing particles in the second aluminum-based material was 60μm.
[0073] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 150 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 6
[0074] In this example, the structure shown in Figures 2 to 4 was used, the first aluminum-based material was made of Al2O3 particles with a volume content of 25% and the remainder Al-1Mg-0.7Si-0.25Cu, and the second aluminum-based material was made of Al2O3 particles with a volume content of 55% and the remainder Al-1Mg-0.7Si-0.25Cu. The average grain size of the Al2O3 particles in the first aluminum-based material was 30 μm, and the average grain size of the Al2O3 particles in the second aluminum-based material was 60 μm.
[0075] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 150 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 7
[0076] In this embodiment, the axially outer wall of the flange and the axially inner wall of the connection part are directly metallurgically joined in the circumferential direction (i.e., no protrusions or receiving openings are provided), the first aluminum-based material is made of Al2O3 particles with a volume content of 30% and the remainder Al-1Mg-0.7Si-0.25Cu, and the second aluminum-based material is made of Al2O3 particles with a volume content of 70% and the remainder Al-1Mg-0.7Si-0.25Cu. The average grain size of the Al2O3 particles in the first aluminum-based material was 40 μm, and the average grain size of the Al2O3 particles in the second aluminum-based material was 100 μm.
[0077] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 150 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Example 8
[0078] In this example, the structure shown in Figures 2 to 4 was used, the first aluminum-based material was made of 30% Si3N4 reinforcing fibers by volume and the remainder Al-0.6Mg-0.9Si, and the second aluminum-based material was made of 30% Si3N4 reinforcing particles by volume and the remainder Al-4Cu-0.8Mg. The aspect ratio of the Si3N4 reinforcing fibers in the first aluminum-based material was 7, and their diameters were 50μm or less, and the average particle size of the Si3N4 reinforcing particles in the second aluminum-based material was 100μm.
[0079] The brake disc for lightweight automobiles was manufactured using a manufacturing method such as steps S110 to S130. As a result of the inspection, the interface bond strength between the cap and the disc body in the brake disc for lightweight automobiles was 150 MPa or more. The brake disc for lightweight automobiles was subjected to a bench test, and two bench tests, T / CAAMTB 09-2018 high load and Jaso C 419-2006 torque destruction, were completed and passed. It was confirmed that the structural strength and friction and wear performance of the brake disc met the requirements for brake discs. Comparative Example 1
[0080] In this comparative example, the structural configurations shown in Figures 2 to 4 were used, the first aluminum-based material was made of 30% by volume of Si3N4 reinforcing fibers and the remainder Al-0.6Mg-0.9Si, and the second aluminum-based material was made of 30% by volume of Si3N4 reinforcing particles and the remainder Al-0.6Mg-0.9Si. The aspect ratio of the Si3N4 reinforcing fibers in the first aluminum-based material was 7, and their diameters were 50μm or less, and the average particle size of the Si3N4 reinforcing particles in the second aluminum-based material was 50μm.
[0081] The manufacturing method of steps S110 to S130 was used to manufacture the product. After sintering was completed, it was found that the shrinkage rate of the first aluminum-based material was larger than that of the second aluminum-based material, and the two aluminum-based materials did not achieve effective metallurgical bonding, resulting in cracks occurring at the interface bonding points. Comparative Example 2
[0082] In this comparative example, the structural form shown in Figures 1 to 3 was used, the first aluminum-based material was made of Al-3Cu-0.8Mg, the second aluminum-based material was made of silicon carbide particles with a volume content of 25% and the remainder Al-4Cu-0.8Mg, and the average particle size of the silicon carbide particles in the second aluminum-based material was 45 µm.
[0083] The brake disc was manufactured using the manufacturing method of steps S110 to S130. A braking effect bench test was conducted in accordance with QC / T 564-2008, and it was found that the heat resistance did not meet the standard due to the low ceramic content in the second aluminum-based material, which is the friction ring of the brake disc, and obvious dents occurred on the surface of the disc body. Comparative Example 3
[0084] In this comparative example, the structural configurations shown in Figures 2 to 4 were used, the first aluminum-based material was made of 20% by volume of Al2O3 reinforcing fibers and the remainder Al-4Cu-0.8Mg, and the second aluminum-based material was made of 50% by volume of Al2O3 reinforcing particles and the remainder Al-0.6Mg-0.9Si. The aspect ratio of the Al2O3 reinforcing fibers in the first aluminum-based material was 10, and their diameters were 50μm or less, and the average particle size of the Al2O3 reinforcing particles in the second aluminum-based material was 45μm.
[0085] The manufacturing method of steps S110 to S130 was used to manufacture the product. After sintering was completed, it was found that the shrinkage rate of the first aluminum-based material was larger than that of the second aluminum-based material, and the two aluminum-based materials did not achieve effective metallurgical bonding, resulting in cracks occurring at the interface bonding points. Comparative Example 4
[0086] In this comparative example, the axially outer wall of the flange and the axially inner wall of the connection part were directly metallurgically joined in the circumferential direction (i.e., no protrusions or receiving openings were provided), the first aluminum-based material was made of Al2O3 particles with a volume content of 30% and the remainder Al-1Mg-0.7Si-0.25Cu, and the second aluminum-based material was made of Al2O3 particles with a volume content of 75% and the remainder Al-1Mg-0.7Si-0.25Cu. The average grain size of the Al2O3 particles in the first aluminum-based material was 40 μm, and the average grain size of the Al2O3 particles in the second aluminum-based material was 100 μm.
[0087] The manufacturing method of steps S110 to S130 was used to manufacture the product. After the sintering was completed, it was found that the first aluminum-based material had shrunk and the second aluminum-based material had obviously expanded, and the two aluminum-based materials did not achieve effective metallurgical bonding, and cracks occurred at the interface bonding sites. Comparative Example 5
[0088] 2 to 4, the first aluminum-based material was made of Al2O3 particles with a volume content of 25% and the remainder Al-1Mg-0.7Si-0.25Cu, and the second aluminum-based material was made of Al2O3 particles with a volume content of 55% and the remainder Al-1Mg-0.7Si-0.25Cu. The average particle size of the Al2O3 particles in the first aluminum-based material was 30 μm, and the average particle size of the Al2O3 particles in the second aluminum-based material was 35 μm.
[0089] The manufacturing method of steps S110 to S130 was used to manufacture the product. After sintering was completed, it was found that the shrinkage rate of the first aluminum-based material was larger than that of the second aluminum-based material, and the two aluminum-based materials did not achieve effective metallurgical bonding in some circumferential regions, resulting in cracks occurring at the interface bonding locations. Comparative Example 6
[0090] 2 to 4, the first aluminum-based material is made of Al2O3 particles with a volume content of 25% and the remainder Al-1Mg-0.7Si-0.25Cu, and the second aluminum-based material is made of Al2O3 particles with a volume content of 55% and the remainder Al-1Mg-0.7Si-0.25Cu. The average grain size of the Al2O3 particles in the first aluminum-based material is 5 μm, and the average grain size of the Al2O3 particles in the second aluminum-based material is 35 μm.
[0091] The brake disc was manufactured using the manufacturing method of steps S110 to S130. A braking effect bench test was conducted in accordance with QC / T 564-2008, and it was found that the wear resistance did not meet the standard due to the fine ceramic particles in the second aluminum-based material, which is the friction ring of the brake disc, and obvious dents were generated on the surface of the disc body. Comparative Example 7
[0092] In this comparative example, the structural configurations shown in Figures 2 to 4 were used, the first aluminum-based material was made of 20% by volume of Al2O3 reinforcing fibers and the remainder Al-0.6Mg-0.9Si, and the second aluminum-based material was made of 50% by volume of Al2O3 reinforcing particles and the remainder Al-4Cu-0.8Mg. The aspect ratio of the Al2O3 reinforcing fibers in the first aluminum-based material was 12, and their diameters were 50μm or less, and the average particle size of the Al2O3 reinforcing particles in the second aluminum-based material was 50μm.
[0093] The manufacturing method was as follows: Steps S110 to S130. Since the fibers in the first aluminum-based material were too thin and long, the reinforcing phase fibers could not be uniformly dispersed in the aluminum-based composite material, which affected the mechanical performance of the first aluminum-based material and the interface structure with the second aluminum-based material, and thus the lightweight brake disc could not be successfully manufactured.
[0094] As can be seen from the comparison of the results of Examples 1-8 and Comparative Examples 1-7, when the same parts are manufactured with materials of different components, the interface bonding effect between different materials must be fully considered. In the powder metallurgy process, the sintering stage determines the performance of the manufactured parts, so if the difference in the sintering shrinkage rate of two kinds of materials is obvious, it will affect the interface bonding effect between the two kinds of materials. Adjusting the sintering shrinkage rate of powder metallurgy materials is related to factors such as the grain size of raw material particles, alloy element content, powder molding pressure and sintering temperature, and process design. The difference in shrinkage rate is essentially the difference in the material densification process in the sintering process, and the present application realizes the synergistic design of the shrinkage rate by controlling the grain size, the content of the reinforcing phase and the content of the alloy element, ensuring that the interface bonding of the two kinds of materials is good, while exerting the performance characteristics of different points, namely, structural strength and wear resistance function.
[0095] Finally, the lightweight automobile brake disc according to the present application is not limited to the structure shown in the above embodiment, and the above embodiment describes only some embodiments of the present invention, and although the description is specific and detailed, it should not be interpreted as limiting the scope of the patent of the present invention. It should be noted that those skilled in the art can make various modifications and improvements to the present invention without departing from the spirit of the present invention, and these modifications and improvements also belong to the scope of the present invention. Therefore, the scope of protection of the patent of the present invention depends on the scope of the attached claims.
Claims
1. A cap and a disk body, a first aluminum-based material and a second aluminum-based material, the first aluminum-based material comprising a ceramic reinforcing phase having a volume content of 0-30% and a remainder being an aluminum alloy matrix, the second aluminum-based material comprising a ceramic reinforcing phase having a volume content of 30%-70% and a remainder being an aluminum alloy matrix, the alloying element content of the aluminum alloy matrix in the first aluminum-based material is equal to or less than the alloying element content of the aluminum alloy matrix in the second aluminum-based material, and when the alloying element content of the aluminum alloy matrix in the first aluminum-based material=the alloying element content of the aluminum alloy matrix in the second aluminum-based material, the volume contents of the ceramic reinforcing phase in the first aluminum-based material and the second aluminum-based material are not equal.
2. 2. The lightweight automotive brake disc according to claim 1, wherein the aluminum alloy matrix is a 2-series or 6-series aluminum alloy.
3. 3. The lightweight automobile brake disc according to claim 2, wherein the 2-series aluminum alloy is an Al-Cu-Mg-based alloy or an Al-Cu-Mg-Si-based alloy, and the 6-series aluminum alloy is an Al-Mg-Si-based alloy.
4. 4. The lightweight automotive brake disc according to claim 1, wherein the ceramic reinforcing phase in the first aluminum-based material is ceramic reinforcing particles or ceramic reinforcing fibers, and when the ceramic reinforcing phase in the first aluminum-based material is ceramic reinforcing particles, the average particle size of the ceramic reinforcing particles in the first aluminum-based material is 10 μm to 40 μm, and when the ceramic reinforcing phase in the first aluminum-based material is ceramic reinforcing fibers, the aspect ratio of the ceramic reinforcing fibers in the first aluminum-based material is 5 to 10 and the diameter of the ceramic reinforcing fibers is 50 μm or less.
5. 5. The lightweight automotive brake disc according to claim 4, characterized in that the ceramic reinforcing phase in the second aluminum-based material is a ceramic reinforcing particle, and the average particle size of the ceramic reinforcing particle in the second aluminum-based material is between 45 μm and 100 μm.
6. 2. The lightweight automotive brake disc according to claim 1, wherein the cap includes a cap body and a flange portion, the disc body includes a friction portion and a connection portion, and an axially outer wall of the flange portion and an axially inner wall of the connection portion are metallurgically joined in the circumferential direction.
7. 7. A lightweight automotive brake disc as claimed in claim 6, characterized in that the axially outer wall of the flange portion is provided with a plurality of protrusions or receiving openings along the circumferential direction, and correspondingly, the axially inner wall of the connection portion is provided with a plurality of receiving openings or protrusions along the circumferential direction, and when the flange portion and the connection portion are metallurgically joined, the protrusions are provided within the receiving openings.
8. 8. The lightweight automotive brake disc according to claim 7, wherein the length direction of the protrusion is parallel to the radial direction of the brake disc or forms an included angle therewith.
9. A method for producing a lightweight automobile brake disc according to any one of claims 1 to 8, providing the first aluminum-based material and a second aluminum-based material; and a step of pre-pressing the first aluminum-based material and the second aluminum-based material, respectively, or pre-pressing one of them and filling the other with powder, followed by laminating, sintering and hot pressing to obtain the lightweight automobile brake disc.
10. The pre-pressure molding pressure is 30 MPa to 70 MPa, and the lamination pressure is 200 MPa to 400 MPa; The sintering conditions are as follows: the temperature is increased to 570°C to 640°C at a rate of 5°C / min to 10°C / min, and the temperature is maintained for 0.5 to 2 hours; 10. The method for manufacturing a lightweight automobile brake disc according to claim 9, wherein the hot press forming is performed at a temperature of 530° C. to 570° C. and at a pressure of 200 MPa to 300 MPa.
Citation Information
Patent Citations
Combined composite brake disc, preparation method and application
CN107100949A
Hybrid lightweight brake disk and production method
US20180209498A1
Thermal management of metal matrix composite systems
US20210364053A1